Arts and Refugees: Multidisciplinary Perspectives - Martiniello, Marco (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book examines the relevance of artistic practices in the current debate about the integration of de facto refugees in Europe, and also in the actual integration of refugee artists into the social fabric and the artistic scene. It looks at the role of arts (music, theatre, literature, etc.) in the solidarity movements in favor of refugees occurring in a number of European cities. It also examines the trajectory of refugee artists and their strategies to claim a position in their new society and artistic scene. The included chapters represent different disciplines and different theoretical perspectives (social movement theories, social mobilization theories, and cultural participation theories